2022
DOI: 10.2147/cia.s378327
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Frailty on Perioperative Outcomes in Patients Receiving Short-Level Posterior Lumbar Interbody Fusion: A Stepwise Propensity Score Matching Analysis

Abstract: Background: There are many studies on the impact of frailty on postoperative complications; however, there are few studies focusing on stepwise propensity score matching (PSM) to offset the influence of age. Methods: We gathered data for patients undergoing short-level posterior lumbar interbody fusion from January to December 2021. According to the Fried frailty phenotype, we categorized patients into non-frail, pre-frail, and frail groups, then, stepwise PSM for age, sex, American Society of Anesthesiologist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Several studies have shown that frailty is a risk factor for a poor prognosis in patients undergoing some types of surgery [ 5 , 6 ]. On the other hand, there is a body of evidence questioning the significance of this method of evaluating patients in this group [ 7 , 8 , 9 , 10 ]. Therefore, the ESC/ESA guidelines for non-cardiac surgery recommend the assessment of frailty in patients at risk of it but mainly highlight the prediction of mortality, emphasising that frailty parameters are included in the NSQIP questionnaire [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that frailty is a risk factor for a poor prognosis in patients undergoing some types of surgery [ 5 , 6 ]. On the other hand, there is a body of evidence questioning the significance of this method of evaluating patients in this group [ 7 , 8 , 9 , 10 ]. Therefore, the ESC/ESA guidelines for non-cardiac surgery recommend the assessment of frailty in patients at risk of it but mainly highlight the prediction of mortality, emphasising that frailty parameters are included in the NSQIP questionnaire [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that “frailty”, an age-related clinical condition characterized by decreased physiological capacity and increased susceptibility to stressors, has been associated with perioperative complications and prognosis in various fields [ 23 , 24 , 25 , 26 ], including spine surgery [ 27 , 28 , 29 ]. Frailty is particularly important in relation to neoplasms, for which frail or pre-frail patients are at increased risk of suffering from perioperative complications, chemotherapy resistance, disease progression, and death [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%